Magnesium Metabolism in 4‐Year‐Old to 8‐Year‐Old Children. (January 2014) - Abrams, Steven A; Chen, Zhensheng; Hawthorne, Keli M
ABSTRACT Magnesium (Mg) is a key factor in bone health, but few studies have evaluated Mg intake or absorption and their relationship with bone mineral content (BMC) or bone mineral density (BMD) in children. We measured Mg intake, absorption, and urinary excretion in a group of children 4 to 8 years of age. Mg absorption was determined using a dual‐tracer stable isotope technique, with 25Mg given intravenously and 26Mg given orally. We found a small, but significantly greater Mg absorption efficiency (percentage absorption) in males than females (67% ± 12% versus 60% ± 8%, p = 0.02) but no difference in estimated net Mg retention (average of 37 mg/d in both males and females). Relating dietary Mg intake to estimated Mg retention showed that an intake of 133 mg/d, slightly above the current estimated average requirement (EAR) of 110 mg/d, led to a net average retention of 10 mg/d, the likely minimum growth‐related need for this age group. Covariate analysis showed that Mg intake and total Mg absorption, but not calcium intake or total absorption were significantly associated with both total body BMC and BMD. These results suggest that usual Mg intakes in small children in the United States meet dietary requirements in most but not all children. Within the usual range of children's diets in the United States, dietary Mg intake and absorption may be important, relatively unrecognized factors in bone health. © 2014 American Society for Bone and Mineral Research.